O uso das metodologias ativas no Ensino de Ciências ofertadas a estudantes com deficiência intelectual do ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This study deals with the topic of inclusion of students with special educational needs (NEEs in Portuguese) in the context of High School in two schools in the State of Goiás. The general objective is to understand how Active Methodologies can be integrated effectively to promote the inclusion of students with Intellectual Disabilities in High School.
The use of active methodologies in science teaching offered to high school students with intellectual disabilities
Keywords: Metodologias ativas; Ensino de Ciências; Deficiência intelectual; Active methodologies; Science teaching; Intellectual disability; TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL; CIENCIAS HUMANAS::EDUCACAO; OUTROS